2019
DOI: 10.9755/ejfa.2019.v31.i3.1919
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Therapeutic Properties of Camel Milk: A Review

Abstract: Camel’s milk is one of the most useful types of milk. Camel’s milk is a white liquid, made up of a combination of emulsified fatty globules mixed with aqueous liquid. Several investigations have shown that camel’s milk is able to treat many diseases even chronic diseases. It also proved that it contains a group of natural elements and compounds that have the special therapeutic ability in internal diseases. This work is aim to highlight and review the chemical composition of camel’s milk and its therapeutic be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 24 publications
(52 reference statements)
0
23
0
Order By: Relevance
“…The low total count of coliform bacteria could also be related to high contents of vitamin C and high pH acidity (Table 2 and Table 4), which inhibit the growth of harmful bacteria and contribute to the longterm preservation of camel's milk as mentioned previously (El Hatmi et al, 2015). Also, camel's milk may contain a number of protective proteins (e.g., lactoferrin, lysozyme, immunoglobulin) (AL-Ayadhi & Halepoto, 2017;Hammam, 2019). In a recent study (Ismaili et al, 2019), about half of the camel's milk samples analyzed contained high total coliform counts due to a lack of refrigeration in milk storage/transportation and noncompliance with hygienic conditions during milking, which indicates an intense microbial contamination, the opposite of the results of this study.…”
Section: Fatty Acid Mineral and Vitamin Analysesmentioning
confidence: 96%
See 2 more Smart Citations
“…The low total count of coliform bacteria could also be related to high contents of vitamin C and high pH acidity (Table 2 and Table 4), which inhibit the growth of harmful bacteria and contribute to the longterm preservation of camel's milk as mentioned previously (El Hatmi et al, 2015). Also, camel's milk may contain a number of protective proteins (e.g., lactoferrin, lysozyme, immunoglobulin) (AL-Ayadhi & Halepoto, 2017;Hammam, 2019). In a recent study (Ismaili et al, 2019), about half of the camel's milk samples analyzed contained high total coliform counts due to a lack of refrigeration in milk storage/transportation and noncompliance with hygienic conditions during milking, which indicates an intense microbial contamination, the opposite of the results of this study.…”
Section: Fatty Acid Mineral and Vitamin Analysesmentioning
confidence: 96%
“…The fat in camel's milk is lower than in cow's milk, and it is a smaller globule that can be easily absorbed and digested. The lower fat content of camel's milk is a benefit for people with heart disease because a build-up of fat in the arteries can lead to strokes (Hammam, 2019). Camel's milk seems to be very different from other mammalian milks consumed by humans in terms of unsaturated fatty acid composition and in its low content of short-chain fatty acids and higher unsaturated fatty acids (Konuspayeva et al, 2008).…”
Section: Fatty Acid Mineral and Vitamin Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Camel milk is a valuable and common source of nutrition in many countries, in which it is different not only in composition but also in function (Alabdulkarim, 2012). It is a rich source of immunoglobulins (G and A), vitamins [A, B 2 , C (highest), and E], and minerals (Na, K, Fe, Cu, Zn, and Mg) while sugar, proteins, and cholesterol are not present in high concentration in camel milk (Hammam, 2019; Mullaicharam, 2014). Also, it contains less quantity of short‐chain fatty acid carotene and a high concentration of long‐chain fatty acids (Al‐Nasseri et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that camel milk is very effective in the treatment of liver disorders to normalize their functions (Darwish et al., 2012). Also, anticancer (Yang et al., 2019), antiallergic (Gizachew et al., 2014), and antidiabetic effects (Hammam, 2019) of camel milk have been proved. In addition, it is highly digestible with antioxidative capability (Ugwu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%